Development of a Combined Measurement System for Torque and Angular Position. (2016) - Menke, T.; Unger, C.; Dai, A.; Kramer, D.; Eilert, B.; Ullmann, G.; Overmeyer, L.
Abstract: In this article a combined contactless measurement method is presented which is based on angle differences. The aim is the development of a combined, optical measurement system to determine the angular position of a shaft and the applied torque on it as well as an appropriate production technology to apply markings. Two independent modules are used which separately allow the measurement of angular position and rotational speed and if combined can measure torque. To ensure a simple integration of the system into any application, position markings are directly applied on the shaft using a laser. The selected technological approach is based on a contactless measurement method using angle differences. The concept as well as first research results are presented.